High-Grade Ectopic Pituitary Adenoma within the Cerebellopontine Angle: A Case Report - Anderson, Cassidy; Sriram, Aishwarya; Funari, Abigail; Hsu, Kevin; Yokoda, Raquel; Pecorari, Isabella; Flaquer, Isabella; Akbar, Nadeem; Colley, Patrick; Basson, Geoffrey; Moskowitz, Howard S.; Agarwal, Vijay (Journal of Neurological Surgery Reports, 2023)
Ectopic pituitary tumors are neoplasms with no connection to the pituitary gland and are commonly deposited in other areas of the anterior skull base. A 32-year-old woman presented with a 3-month history of right-sided facial weakness, sensorineural hearing loss, diplopia, and severe headaches. Physical examination revealed a mid-dilated sluggishly reactive right pupil with slight limitation in all gazes, as well as right-sided orbicularis weakness, lagophthalmos, and decreased facial sensation. A magnetic resonance imaging (MRI) of the head without contrast revealed a 3.7 × 1.8 × 2.6 cm mildly enhancing mass in the right internal acoustic meatus and along the petrous ridge. The case was brought before the institution's tumor board, where concern for higher grade pathology, such as hemangiopericytoma, was discussed. Per patient preference, surgical biopsy of the tumor was performed. Immunohistochemical staining revealed a World Health Organization (WHO) grade II neuroendocrine tumor, with cells staining positive for synaptophysin, chromogranin, and CD56, with a Ki-67 index of 8%. In addition to the ectopic location, this pituitary tumor was noted to be aggressive in nature based on its high Ki-67 index. Surgical excision and radiologic therapy of tumors involving the CPA are appropriate treatments in most cases.
Keywords: ectopic pituitary tumor; neuroendocrine tumor; cerebellopontine angle tumor